The construction of nostalgia in screen media in the context of postsocialist China - Gu, Zhun (2019)
This thesis explores how different forms of nostalgia have been constructed by various forms of screen media in China since the 1990s. Textual analysis of media languages and structures and discourse analysis of the Chinese government’s economic-politics are used to examine the relationship between screen nostalgia, the influence of the Chinese Communist Party (CCP), China’s neoliberalist capitalism, and China’s media internationalisation. In order to examine the complex relationship between socio-economic and political contexts and nostalgic screen cultures produced by various generations of producers and presented in different formats of screen media, this thesis will investigate diverse forms of screen media texts in film, Internet drama and TV documentary. The following screen media texts are chosen: five feature films, A Mongolian Tale (Xie Fei, 1995), Nuan (Huo Jianqi, 2003), Shower (Zhang Yang, 1999), 24 City (Jia Zhangke, 2008), and So Young (Zhao Wei, 2013); one Internet drama, With You (Liu Chang, 2016); and two television documentaries A Bite of China (Chen Xiaoqing, 2012) and Maritime Silk Road (Zhang Wei, 2016).